(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2024)
This study focuses on the impact of climate change on Arctic fox populations using mathematical modeling. The research employs a basic Lotka-Volterra-style model to simulate the effects of temperature, precipitation, and snow cover on the Arctic fox population dynamics. The model is based on the assumption that the population growth rate is limited by the carrying capacity of the environment and is influenced by these environmental factors. The study provides insights into the complex relationship between environmental factors and population changes, highlighting the need for more sophisticated models to holistically understand the impact of climate change on ecosystems. The findings underscore the importance of mathematical models in guiding adaptive strategies for ecosystem management amidst changing climates, emphasizing the necessity for further research to comprehensively address climate-induced challenges and ensure a sustainable future for ecosystems and species.